Peningkatan Literasi Perpajakan Melalui Brevet Pajak A dan B Bagi Mahasiswa dan Pelaku UMKM - Listya Ningrum; Siti Nuridah; Dyah Shinta Kusumaningtyas; Eka Yulianto; Selly Mutia Nurivani (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
Low tax literacy among prospective workers and micro, small, and medium enterprises (UMKM) is a serious challenge in efforts to increase voluntary tax compliance in Indonesia. Lack of understanding of technical calculation and reporting procedures often leads to administrative errors that are detrimental to taxpayers. This community service activity aims to equip students and MSMEs with practical competencies through Tax Brevet A and B training. The implementation method is carried out through three main stages: (1) Socialization of theoretical material on Personal Income Tax, Corporate Income Tax, and Value Added Tax (VAT), (2) Practical workshops on filling out periodic and annual tax returns using e-SPT and e-Filing application simulations, and (3) Interactive discussions based on case studies of minor tax disputes. The results of this activity show a very significant increase in participant understanding. Based on evaluation data, the average score of participants increased from 55.00 in the pre-test to 82.50 in the post-test. This training not only adds value to students' professional portfolios but also provides a foundation for UMKM to implement more orderly and accountable tax management.